A framework for evaluating instructional design models resulting in a model for designing and developing computer based learning tools with GIS technologies - Stott, Deborah Ann (Rhodes University, Faculty of Education, Department of Education, 2005)
With the increasing pressures and concerns in education regarding capability, lifelong learning, higher order cognitive skills, transdisciplinary education and so on, educators are seeking fresh ways to teach and new tools to support that teaching. In South Africa, Outcomes Based Education (OBE) has identified critical outcomes (skills) across all subject areas such as problem solving, teamwork, fostering critical thinking etc. as a way of responding to these pressures and concerns. But OBE has been criticised for lacking the necessary tools to develop these critical skills and to promote cross-discipline learning. One innovative way of offering transformative teaching, instruction and learning that may foster the development of these critical skills, particularly those concerned with critical thinking, is by using geographic information systems (GIS) technologies. The scope for using these technologies in secondary education is now being realised for teaching the more generic, cross-discipline skills described whereby students are learning not only about GIS but also with GIS. This realisation provides the opportunity to create flexible, computer-based learning materials that are rooted in authentic, real-world contexts, which aim to enhance the cognitive skills of the students. If these technologies can be used in an innovative way to develop critical outcomes and skills, a model needs to be defined to aid the design and development of learning materials using these technologies for use in schools. The primary aim of this study has been to develop such a model; a model which emphasises the development of real-world learning materials that develop higher-order thinking skills in learners. Another key product of this study is the submission of a comprehensive yet flexible framework for evaluating instructional design models found in the educational literature in order to determine if these design models can be used to develop learning materials forparticular contexts.
Keywords: Computer-assisted instruction; Geographic information systems; Education, Secondary -- Computer network resources; Educational innovations